Hope and expectancies for future events in depression - Thimm, Jens C.; Holte, Arne; Brennen, Tim; Wang, Catharina Elisabeth A. (Frontiers in Psychology, 2013)
The present study investigated prospective cognition with the Hope scale (Snyder et al., 1991) and the Unrealistic Optimism Scale (Weinstein, 1980) in clinically depressed (CD; n = 61), previously depressed (PD; n = 42), and never depressed controls (ND; n = 46). In line with previous research, significant negative correlations between hope and symptoms of depression were found. Previously depressed reported lower levels of hope than NDs, but were more hopeful than CDs. In addition, relationships between depressive symptoms, dysfunctional attitudes, and expectations for the future were examined. As hypothesized, the CDs estimated their probability of experiencing positive events in the future as lower and their probability of experiencing negative events as higher than the two other groups. The PDs differed not from the NDs in their probability estimates. Implications of the findings are discussed.